Microstructural Parameters of HPMC/PVP Polymer Blends Using Wide Angle X-Ray Technique - Prakash, Y.; Mahadevaiah, D; Somashekarappa, H.; Demappa, T.; Somashekar, R. (Journal of Research Updates in Polymer Science, 2012)
Hydroxypropylemethylecellulose (HPMC) and Polyvinylpyrrolidone (PVP) polymer virgin and blend films were prepared and investigated using wide angle X-ray scattering method. Microstructural parameters like lattice strain (g %), the crystallite size for individual the Bragg’s reflection (hkl) have been computed using line profile analysis and hence by whole pattern fitting method. The X-ray diffraction study reveals that the blending of PVP decreases the crystallanity of HPMC up to 5:4 concentration and then increases. Measured tensile strength decreases, Young’s Modulus decreases, and % elongation increases as the concentration of PVP increases. The surface morphology investigated using scanning electron microscope, shows that the two polymers were miscible in all concentration range.